Representation Wars: Enacting an Armistice Through Active Inference - Constant, Axel; Clark, Andy; Friston, Karl J. (Frontiers in Psychology, 2021)
Over the last 30 years, representationalist and dynamicist positions in the philosophy of cognitive science have argued over whether neurocognitive processes should be viewed as representational or not. Major scientific and technological developments over the years have furnished both parties with ever more sophisticated conceptual weaponry. In recent years, an enactive generalisation of predictive processing – known as active inference – has been proposed as a unifying theory of brain functions. Since then, active inference has fuelled representationalist and dynamicist campaigns. However, we believe that when diving into the formal details of active inference, one should be able to find a solution to the war; if not a peace treaty, surely an armistice of sort. Based on an analysis of these formal details, this paper shows how both representationalist and dynamicist sensibilities can peacefully coexist within the new territory of active inference.